The effect of good corporate governance mechanisms on accounting conservatism with leverage as a moderating variable - Ain Hajawiyah; Agus Wahyudin; Kiswanto; Sakinah; Indra Pahala (Cogent Business & Management, 2020)
This study aims to analyze the effect of good corporate governance mechanisms (institutional ownership, managerial ownership, and independent commissioners) on accounting conservatism with leverage as a moderating variable. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2016 are the population in this study, which consists of 135 companies. The samples are selected with some criteria which result in 33 firms each year (99 units of analysis). The data are analyzed using moderated regression analysis with a test of absolute difference values using SPSS software. This study shows that institutional ownership and independent commissioners have a significant positive effect on accounting conservatism, while managerial ownership has a significant negative effect on accounting conservatism. Leverage moderates the effect of managerial ownership and independent commissioner on accounting conservatism but do not moderate the effect of institutional ownership on accounting conservatism. This study concludes that good corporate governance mechanisms that have been implemented can affect accounting conservatism practice in the company.
Keywords: 650